Cleft Palate in Newborns Diagnosed With Prematurity. (23rd March 2021) - Shehan, Jennifer N.; Danis, David O'Neil; Bains, Ashank; Basa, Krystyne; Marston, Alexander P.; Levi, Jessica R.
Abstract : Objective: Cleft lip and/or palate (CLP) is the most common major congenital malformation of the head and neck. Although numerous genetic features, syndromes, nutritional deficiencies, and maternal exposures have been implicated in the etiology of CLP, the impact of prematurity on the pathogenesis remains incompletely understood. This study seeks to evaluate the associations between prematurity and the development of CLP in the United States. Study Design: Cross‐sectional. Setting: Academic medical center. Methods: The Kids' Inpatient Database (2016) was used to identify weighted in‐hospital births with diagnoses of prematurity or CLP. Demographic information was obtained. Odds ratios were used to determine associations between prematurity and CLP. Results: Among patients included in our data set, 8.653% (n = 326, 147) were preterm; 0.136% (n = 5115) had CLP; and 0.021% (n = 808) were preterm and had CLP. Preterm infants had 1.90 times the odds (95% CI, 1.74‐2.07) of developing CLP when compared with the nonpreterm population. The binary logistic regression model accounting for possible confounding variables produced an odds ratio of 1.83 (95% CI, 1.66‐2.01) for the association between prematurity and CLP. Conclusion: Infants who are born preterm are more likely to have CLP than full‐term infants. The current results will allow for improved risk stratification, maternal counseling, and interventions in the case of prematurity. Level of Evidence: 4.